Bloody Friday (Module II, 2013)
Northern Ireland. Belfast. Footage of a large explosion on a street lined with shops, shows debris flying and a large plume of black smoke rising (one of a total of 22 explosions that day by the Provisional IRA, which killed 19 civilians). Close shots of fires breaking out in the buildings. Cars speed away.Debris flying through air and black smoke from another explosion. Troops crouched behind bus and Armed British soldiers in the street.Footage of a bomb exploding on a residential street.Fire fighter putting out buses on fire at bus station.British soldiers and commander along street.